O wariantach kaliskiej edycji Wojny domowej Samuela Twardowskiego - Kuran, Michał (Acta Universitatis Lodziensis. Folia Librorum, 2010)
This article presents the problems with establishing a foundation for the edition titled Civil War by S. Twardowski. Before World War II, Part One was a Cracow published text from 1660 parts two-four were in manuscript form. Due to the destruction of the manuscript, Jesuits currently published a censored edition which does not take into account Kalisz’s edition from 1681. The Kalisz edition has a few variants that are primarily found on pages 1-24 of the second part of this work. Their considerable scope proves that these pages were folded twice. There is also a variant in the title represented by a copy in the Library of Warsaw. The activities of the Jesuits show considerable consideration about the quality of the published volume Civil War and wanted to celebrate the 20th anniversary of the poet's death and establish a teaching program in their colleges.